2014
DOI: 10.1038/ijo.2014.112
|View full text |Cite
|
Sign up to set email alerts
|

Ileal brake activation: macronutrient-specific effects on eating behavior?

Abstract: Apart from lipids, also sucrose and casein reduce food intake on ileal infusion, thereby activating the ileal brake. In addition to food intake, also satiety and GI peptide secretion were affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 38 publications
3
84
0
Order By: Relevance
“…Ithasrepeatedlybeenshownthatinfusionofnutrientsinvarious parts of the small intestine results in a reduction in food intake (24)(25)(26). All of these studies have been performed with different macronutrient compositions and caloric densities.…”
Section: Gastrointestinal Peptidesmentioning
confidence: 99%
“…Ithasrepeatedlybeenshownthatinfusionofnutrientsinvarious parts of the small intestine results in a reduction in food intake (24)(25)(26). All of these studies have been performed with different macronutrient compositions and caloric densities.…”
Section: Gastrointestinal Peptidesmentioning
confidence: 99%
“…3A). This time sequence could be relevant to the body and eating of a meal because starch may be digested over the course of 6 h or more, considering that the stomach residence time of meals may range up tõ 4 h for gastric half-emptying time plus the additional residence time of food in the small intestine (33)(34)(35). Transformation of the small intestine enterocytes could also set up the distal cells for efficient digestion of the next meal starch.…”
Section: Discussionmentioning
confidence: 99%
“…Ileal brake activation induces enhanced satiety signals, satiation and reduction of energy intake [1,2]. Recently, we have shown that not only ileal appearance of lipid but also of the other macronutrients, carbohydrate (sucrose) and protein (casein), results in increased satiation and a reduction of food intake [3]. This reduction in food intake underlines the relevance of the ileal brake as potential food based strategy in the prevention or treatment of overweight and obesity.…”
Section: Introductionmentioning
confidence: 92%
“…The aim of this study was to investigate the effects of intraileal native protein infusion on digestion, AA absorption and immune activation. This was done in a study evaluating the effects of intraileal infusion of native protein on food intake previously performed by our group [3]. It was hypothesized that ileal infusion of native casein results in plasma appearance of AAs in casein and does not result in acute adverse effects such as incomplete digestion of casein protein or inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation